Bioactivities of Digera muricata (L.) Mart. Available in Bangladesh (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Abstract not availableDhaka Univ. J. Pharm. Sci. 16(2): 251-254, 2017 (December)